COVID-19 pandemic in Nepal: Emerging evidence on the effectiveness of action by, and cooperation between, different levels of government in a federal system - Adhikary, Pratik; Balen, Julie; Gautam, Sujan; Ghimire, Sachin; Karki, Jiban Kumar; Lee, Andrew CK; Marahatta, Sujan Babu; Panday, Sarita; Pohl, Gerda; Rushton, Simon; et al. (Journal of Karnali Academy of Health Sciences, 2020)
A new coronavirus disease (COVID-19) caused by a novel pathogen (SARS-CoV-2) spread rapidly around the world in early 2020, and it was declared a pandemic by the World Health Organization (WHO) on 11 March. COVID-19 continues to have a large impact on individuals, societies, and on national health systems across the globe. Due to its novelty and impact, it has challenged all health care systems. The ways in which governments and health systems have responded have varied widely across the world. In the case of Nepal, the pandemic represented a major test for the newly decentralised health system, created as a result of the implementation of the 2015 federal constitution. This paper forms a part of our large on-going study of the decentralisation of the country’s health system. The study is run by the Universities of Sheffield, Huddersfield and Bournemouth in the UK and PHASE Nepal and Manmohan Memorial Institute of Health Sciences in Nepal, and is funded by the UK Health Systems Research Initiative. This paper presents some of the early evidence (as of July 2020) on the effectiveness of the actions taken by Federal, Provincial and Local Governments and the levels of cooperation and coordination between them.